Pembelajaran Reciprocal Teaching Model dengan Strategi Motivasi ARCS Mampu Meningkatkan Hasil dan Kemandirian Belajar Siswa Kelas XI PMS 2 SMKN 1 Lumajang - Susiyati Susiyati (FKIP Universitas Islam Jember, 2018)
The purpose of this study is to improve students’ learning outcomes and learning independence through the Reciprocal Teaching Model by applying ARCS motivational strategies. The research was conducted at SMK 1 Lumajang. The research subjects were students of class XI PMS 2 on 36 Productive Marketing Subjects. The study consisted of three cycles carried out on the 1st, 8th and 15th February 2018 even semester 2017/2018. Students’ independence during teaching and learning increases. Students' independence at a minimum of cycles I, II and III were respectively 17; 50; 50 and the averages were respectively 60.2; 83.3; 88.4. The results of formative test show an improvement in learning outcomes. Students’ learning outcomes from cycle I to cycle III occured a shift in the students’ score distribution. The lowest scores of cycle I, II, III were 50; 55 and 70. The highest scores of cycles I, II, III were 80; 90 and 100. Keywords: Reciprocal Teaching Model, ARCS, Learning Outcomes and Learning Independence